Justice and fairness in international negotiation - Albin, Cecilia (Cambridge studies in international relations, 2001)
"International negotiations have become increasingly significant in international affairs, as the number of parties involved have grown, and regional and global decision-making fora have multiplied. Cecilia Albin examines the role of considerations of justice and fairness in these negotiations. She asks when and why parties act on such considerations, how they are defined and operationalised, and what impact they have upon actual decision-making. She argues that negotiators do not simply pursue their narrow interests or those of their countries, but regularly take principles of justice and fairness into account. These principles come into play at an early stage, as talks are structured and agendas set; in the bargaining process itself; and in the implementation of and compliance with agreements. The analysis is based on cases in four important areas: the environment (air pollution); international trade (the GATT/WTO); ethnic conflict (the Israeli-Palestinian conflict); and arms control (nuclear non-proliferation). Drawing on a mass of empirical data, including a large number of interviews, this book relates the abstract debate over international norms and ethics to the realities of international relations."--Jacket.